ChemInform Abstract: Diels—Alder Reactions of Masked o‐Benzoquinones with 1‐Vinylcyclohexenes: A Short and Efficient Entry to Highly Functionalized Decahydrophenanthrene Skeleton. Issue 7 (29th January 2015) - Niu, Guang‐Hao; Hou, Chieh‐Shen; Chuang, Gary Jing; Wu, Chi‐Phi; Liao, Chun‐Chen
Abstract Masked o‐benzoquinones generated in situ from o‐methoxyphenols and methanol undergo Diels—Alder reaction with 1‐vinylcyclohexenes to provide decahydrophenanthrenes along with bicyclo[2.2.2]octenone derivatives.